Amylatic Activity of Agaricus and Moulds for the Production of Bioethanol - Uddin, M. Rakib; Ferdous, Kaniz; Md. Arifur, Rahman; Anup, K. Roy; Khan, Maksudur R. (Science and Education Publishing, 2013)
Fermentation of potato and carambola juice was investigated using Molds and Agaricus as a potential source of amylase. The amylatic activity of Moulds and Agaricus were studied and the effects of different parameters, such as starch concentrations, pH, incubation time, temperature were investigated. The maximum enzyme activity obtained for Moulds were 173 to 178U/g under the optimum conditions of an incubation period of 30min, 1.5 % starch solution, an incubation temperature of 60°C and a pH of 5.0. For Agaricus, the highest amylase production was 14 to 16U/g using 1.5 % starch solution, pH of 6.0 incubated at 75°C for 30 minutes. Reducing sugar was produced by fermentation of potato and carambola juice using mold and saccarification was conducted for production of bioethanol using yeasts. The ethanol produced from potato and carambola was approximately 11% (v/w) and 5% (v/v) respectively.